AUTHORITY OF THE BUNDER VILLAGE GOVERNMENT IN IMPROVING THE QUALITY OF VILLAGE EDUCATION - Sugiyanto Sugiyanto; Farhan Kamil (TRUNOJOYO LAW REVIEW, 2022)
Education is the guidance or help given by adults to the development of the child to reach his maturity with the aim that the child is quite capable of carrying out his own life tasks not with the help of others. and planned to create a learning atmosphere and learning process so that students actively develop their potential to have religious spiritual power, self-control, personality, intelligence, noble character, and the necessary skills of themselves and society. Conceptually, the term authority or Authority is a very important part of Governance Law (Administrative Law), because the new government can carry out its functions on the basis of the authority it obtains.